The MINI REVIEW: PREPARASI BIOETANOL BERBASIS MAKROALGA - Solle, Clara Indriani; Riwu, Defmit B.N.; Neolaka, Yantus (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2025)
In the face of serious impacts of greenhouse gas emissions and dependence on fossil fuels, biofuels especially bioethanol are emerging as a promising alternative. This article highlights the potential of macroalgae as bioethanol feedstock due to its advantages of abundant availability, rapid growth and high carbohydrate content. The bioethanol production process from macroalgae includes pretreatment, hydrolysis, fermentation and distillation stages. Pre treatment aims to increase the accessibility of cellulose, hydrolysis converts cellulose into glucose which is then fermented into bioethanol by microorganisms such as Saccharomyces cerevisiae. Macroalgae shows very high bioethanol yield compared to other feedstocks making it a sustainable option that does not compete with food production. Bioethanol from macroalgae can be used as transportation fuel, feedstock for chemical industry as well as fuel additive. The use of bioethanol contributes to the reduction of dependence on fossil fuels and supports a more sustainable industry.